The excitation mechanisms of X-ray oxygen emission-lines. Issue Volume 15:Issue S359(2020) (March 2019) - Reynaldi, Victoria; Guainazzi, Matteo; Bianchi, Stefano; Andruchow, Ileana; García, Federico; López, Iván; Salerno, Nicolás
Abstract: We present the Catalogue of High REsolution Spectra of Obscured Sources (CHRESOS) from the XMM-Newton Science Archive. It comprises soft X-ray emission-lines from C to Si and the Fe 3C and Fe 3G L-shell transitions. Here, we concentrate on the oxygen emission-lines O VII(f) and O VIII Lyα to shed light onto the physical processes with which their formation can be related to: active galactic nucleus vs. star-forming regions. We are analysing the relationships between the oxygen lines and the luminosities of: [OIII]λ5007, [OIV]25.89 μ m, MIR-12 μ m, FIR-60 μ m, FIR-100 μ m, and hard X-rays continuum bands.